Global Trends in Social Inclusion and Social Inclusion Policy: A Systematic Review and Research Agenda - Anis Ben Brik (19239442) (2024)
As pressures build, this study can serve as a guidepost for scholars and policymakers to learn from global trends in social inclusion and social inclusion policy. Our systematic review of global trends in social inclusion and social inclusion policy points to the general expansion and retrenchment of social inclusion policy amid increasing social exclusion associated with trends such as globalisation and neoliberalism. In the absence of recent, detailed case descriptions of social inclusion policy at the national level, we call for a renewed scholarly focus on case studies of social inclusion policy. We also discuss the likelihood that persistent climate change, migration, ageing populations, and technological innovations are poised to dramatically influence global social inclusion and suggest that future research should seek to understand the relationship between these developments and social inclusion. As we look to the future and the growing needs of excluded populations, we aim to use this study to learn from and build on these global trends to promote the inclusion of excluded groups around the world. Other Information Published in: Social Policy and Society License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1017/s147474642400054x